Cisplatin, vinblastine, and bleomycin in inoperable non-small cell lung cancer. Issue 5 (May 1985) - Stuart-Harris, R; Fox, R M; Raghavan, D; Coates, A S; Hedley, D; Levi, J A; Woods, R L; Tattersall, M H
Abstract : Forty two patients with inoperable non-small cell lung cancer were entered into a phase II study of the combination chemotherapy regimen PVB (cisplatin 60 mg/m2 by intravenous infusion over two hours on day 1, vinblastine 4 mg/m2 by intravenous bolus on days 1 and 2, and bleomycin 15 mg intramuscularly on days 1, 8, and 15), repeated at three weekly intervals. Twelve of 40 evaluable patients (30%) achieved partial responses; there were no complete responses. The median duration of response was 16 weeks (range greater than 8-73 weeks). The median survival of responding patients calculated from entry to the study until death (40 weeks) was superior to that of patients failing to respond (15 weeks). Treatment was accompanied by signs of moderate toxicity, particularly myelosuppression, nausea and vomiting, alopecia, and neuropathy. One patient died from a neutropenic infection. PVB is a moderately toxic regimen for non-small cell lung cancer and appears similar in efficacy and toxicity to high dose cisplatin and vindesine.